Synthesis and characterization of two Cu(II) complexes with a new pyrazole-based Schiff base ligand: crystallography, DNA interaction and antimicrobial activity of Ni(II) and Cu(II) complexes. Issue 10 (18th May 2016) - Mandal, Susmita; Sadhukhan, Ratan; Ghosh, Utpal; Mandal, Soumik; Saha, Manan; Butcher, Ray J.; Saha, Nitis Chandra
Abstract: Reaction of Cu(II) nitrate with a new pyrazole-based Schiff base ligand, 5-methyl-3-formylpyrazole-N-(2′-methylphenoxy)methyleneimine (MPzOA), afforded two types of Cu(II) complexes at different reaction temperatures, [Cu(MPz OA)(NO3 )]2 (1 ) and [Cu(3, 7, 11, 15-tetramethylporphyrin)(H2 O)](NO3 )2 (2 ), reported together with a Ni(II) complex, [Ni(MPzOA)2 (H2 O)2 ]Br2 (3 ). The compounds are characterized by single crystal X-ray structure analyses along with several physico-chemical and spectral parameters. Complex1 is authenticated as a bis(μ-pyrazolato)dicopper(II), while2 is a porphyrinogen and3 is a distorted octahedral complex. Structural analyses of the complexes reveal that1 crystallized in monoclinic P2 1 /n space group while2 and3 crystallized in monoclinic C2/c space group. DNA-binding studies of the complexes have shown that the complexes interact with CT-DNA. DNA-cleavage studies with plasmid DNA have shown that1 and2 induce extensive DNA cleavage in the presence of H2 O2 as an additive, whereas there is no change in degradation of super-coiled DNA by3 in the presence of additive. The antimicrobial studies of the complexes against Escherichia coli DH5α bacteria strain indicated that all the complexes were capable of killing E. coli with different LD50 values. Abstract :